PARE0022 First National Osteoarthritis Patients Survey in France: Patients Insights First!. (10th June 2014) - Grange, L.; Rannou, F.; Berembaum, F.; Richette, P.; Beroud, F.; Chaussier-Delboy, A.; Chevalier, X.; Dreux, C.; Joseph, P.A.; Roques, C.; Sautet, A.; Srour, F.; et al.
Abstract : Background: The (French) National osteoarthritis Alliance was created in 2011 to otpimise osteoarthritis patient care. Objectives: One of its first initiative was the launch of a national patient survey in December 2012 to assess the main impacts and consequences of osteoarthritis in daily life. In addition to gathering patient needs, the results are expected to be able to sensibilise health authorities, and the public, about osteoarthritis patient's realities. Whilst a true public health issue, osteoarthritis is nonetheless not a priority in prevention or support in national or local health decisions. Methods: A self administered questionnaire was developed by experts of the National osteoarthritis Alliance. The questionnaire addressed previously unexplored issues. The survey consisted of 113 questions and was tested and validated by patients before being put on line at www.stop-arthrose.org . Results: More than 70% of the 2, 914 respondents were aged between 50 and 69 y old. Contrary to common perception, more than a third of them suffered with the first signs of osteoarthritis before the age of 40. Amongst the osteoarthritis worsening factors, overweight and obesity were present for 52, 5% of the respondents, having a professional activity which impacts joints (49, 7%) or previous joint trauma (31, 8%). The more affected joints were (decreasingly ordered) the knees, the hands, the hips and the feet. Respondents describe a negative impact of osteoarthritis on many life aspects, notably mood (81, 7%), leisure activities (77, 2%), professional activity (70, 8%), walking (66, 5%), self image (63, 5%) and family life (59, 4%). The results are also compiled in a brochure "osteoarthritis: experiences and needs of affected people" which is available on the Internet site www.stop-arthrose.org Conclusions: One of the first limits of this survey is its distribution, which was only available for proactive, information seeking internet users. Nonetheless, the results assist in better understanding patient experience, needs and profiles, This innovative survey is a first important step to better recognise osteoarthritis as experienced by patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4109